2007
DOI: 10.3317/jraas.2007.028
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of the direct renin inhibitor aliskiren and ramipril alone or in combination in patients with diabetes and hypertension

Abstract: Objective. To assess the antihypertensive efficacy and safety of the combination of the direct renin inhibitor aliskiren and ramipril in patients with diabetes and hypertension. Methods. In this double-blind, multicentre trial, 837 patients with diabetes mellitus and hypertension (mean sitting diastolic blood pressure [BP] > 95 and < 110 mmHg) were randomised to once-daily aliskiren (150 mg titrated to 300 mg after four weeks; n=282), ramipril (5 mg titrated to 10 mg; n=278) or the combination (n=277) for eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
181
2
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(194 citation statements)
references
References 28 publications
6
181
2
5
Order By: Relevance
“…Ramipril 10 mg was associated with small increases in trough PRA and no Sustained BP reduction beyond 24 h with aliskiren P Palatini et al significant changes in PRC at days 42 and 63. The lack of effect of ramipril on PRC at 24 h after dose is inconsistent with findings from previous studies with ramipril 10 mg, 9,16 and may be a chance finding related to the relatively small number of patients who underwent biomarker assessments in the ramipril group. Previous studies have shown that the BP-lowering effects of aliskiren last beyond the 24-h dosing interval in patients with hypertension.…”
Section: Discussioncontrasting
confidence: 94%
“…Ramipril 10 mg was associated with small increases in trough PRA and no Sustained BP reduction beyond 24 h with aliskiren P Palatini et al significant changes in PRC at days 42 and 63. The lack of effect of ramipril on PRC at 24 h after dose is inconsistent with findings from previous studies with ramipril 10 mg, 9,16 and may be a chance finding related to the relatively small number of patients who underwent biomarker assessments in the ramipril group. Previous studies have shown that the BP-lowering effects of aliskiren last beyond the 24-h dosing interval in patients with hypertension.…”
Section: Discussioncontrasting
confidence: 94%
“…One study assessed the effects of aliskiren compared with ramipril or the agents combined for 8 weeks in patients with diabetes and hypertension. 28 Aliskiren monotherapy provided a superior reduction in msSBP compared with ramipril monotherapy. Combination therapy with aliskiren and ramipril provided superior msSBP reductions compared with either component monotherapy.…”
Section: Discussionmentioning
confidence: 98%
“…14,15,[17][18][19][20][21][22] Data were analysed for aliskiren 150 mg and 300 mg (the US Food and Drug Administration and European Union approved doses for the treatment of hypertension) and placebo after 8 or 12 weeks of treatment for the subgroups of women and men. All of the trials were 8 weeks in duration, except for the aliskiren vs ramipril (6 months) and aliskiren vs HCT (12 months) studies.…”
Section: Methodsmentioning
confidence: 99%
“…For inclusion in the aliskiren/ramipril study, 21 patients also had to have type I or type II diabetes mellitus. In all of the studies, patients with severe hypertension (msDBPX110 mm Hg and/or mean sitting systolic BP (msSBP) X180 mmHg), a history or evidence of secondary hypertension, or a history of severe cerebrovascular or CVD were excluded.…”
Section: Patientsmentioning
confidence: 99%